2012
DOI: 10.1007/s00296-012-2507-0
|View full text |Cite
|
Sign up to set email alerts
|

A manual therapy intervention improves symptoms in patients with carpal tunnel syndrome: a pilot study

Abstract: In carpal tunnel syndrome (CTS), manual therapy interventions (MTI) reduce tissue adhesion and increase wrist mobility. We evaluated the efficacy of a MTI in relieving CTS signs and symptoms. Twenty-two CTS patients (pts) (41 hands) were treated with a MTI, consisting in 6 treatments (2/week for 3 weeks) of soft tissues of wrist and hands and of carpal bones. Pts were assessed for hand sensitivity, paresthesia, hand strength, hand and forearm pain, night awakening; Phalen test, thenar eminence hypotrophy and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…A significant increase in hand grip strength and normalization of motor and sensory latancies were noted. In a recent study comparable with ours (22), after therapy with six sessions of soft tissue and CBM demonstrated that a significant benefit was maintained in pain, Boston symptom severity, and functional scales, whereas there were no changes in electrophysiologic parameters. Burke et al (23) investigated Granston instrument-assisted soft tissue mobilization twice a week for 4 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…A significant increase in hand grip strength and normalization of motor and sensory latancies were noted. In a recent study comparable with ours (22), after therapy with six sessions of soft tissue and CBM demonstrated that a significant benefit was maintained in pain, Boston symptom severity, and functional scales, whereas there were no changes in electrophysiologic parameters. Burke et al (23) investigated Granston instrument-assisted soft tissue mobilization twice a week for 4 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…The techniques that treated adjacent soft tissues include manual therapy techniques, consisting of mobilization of the soft tissue and the fascia, similar to our study. 19,47 The possible explanation for the better results obtained using this kind of approach are the relationships between the different musculoskeletal structures, which have been demonstrated for between the palmar fascia, transverse ligament, flexor retinaculum and antebrachial fascia. 22,48 As has been demonstrated, there is not only an alteration in the nerve tissues, but also in the adjacent soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with symptoms of pain, numbness, or tingling in the median nerve distribution area of hand visited Department of Rehabilitation Medicine, Sun Yat-sen Memorial Hospital, from February 2016 to May 2017. After confirmation by physical and electrophysiological inspection, 51 patients (51 wrists) meeting the following criteria were recruited [23]: (1) pain, numbness, or tingling in the median nerve distribution area of hand, (2) nocturnal worsening of the symptoms, (3) positive Tinel and/or Phalen sign, (4) a slower median nerve conduction (SNCV≦50 m/s and/or DML≧4 ms), (5) patients with unilateral disease, and (6) the desire of the participant to have either a steroid injection or steroid injection plus MSN release. Patients were excluded from this study for the following: (1) symptomatic CTS because of diabetes, thyroid disease, or rheumatic disease, (2) cervical radiculopathy or other polyneuropathy, (3) age<18 years, (4) pregnancy, (5) steroid injection for CTS in the preceding 6 months, (6) history of wrist fracture, (7) prior carpal tunnel decompressive surgery, (8) the presence of infection or skin lesion at the site of injection, (9) patients with bilateral disease, and (10) refusal of informed consent or inability to participate in follow-up.…”
Section: Methodsmentioning
confidence: 99%